2020 17th International Multi-Conference on Systems, Signals &Amp; Devices (SSD) 2020
DOI: 10.1109/ssd49366.2020.9364130
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Sliding Mode Controller for Reducing Torques Applied to a Rehabilitation Robot

Abstract: Exoskeletons are the most efficient devices used to help children, suffering from several diseases, to walk compared to the use of wheelchairs. In rehabilitation, relearning to walk is very important. In fact, repetitive tasks improve human locomotory performances. This paper aims to deal with the control problem of a two degrees of freedom lower limb exoskeleton. During the control process, high torques are considered as a major constraint. Thus, a fuzzy sliding mode controller is implemented. Moreover, stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Maalej et al [14] applied a fuzzy sliding mode controller to manage control issues in a 2-DOF lower limb exoskeleton. Two fuzzy systems supervised sliding mode controllers, ensuring accurate trajectory tracking.…”
Section: Fuzzy Logic Controller (Flc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Maalej et al [14] applied a fuzzy sliding mode controller to manage control issues in a 2-DOF lower limb exoskeleton. Two fuzzy systems supervised sliding mode controllers, ensuring accurate trajectory tracking.…”
Section: Fuzzy Logic Controller (Flc)mentioning
confidence: 99%
“…According to the [14], the dynamics of such a robotic system can be approximated by the following form:…”
Section: Dynamics Modelingmentioning
confidence: 99%
“…(Almaghout et al, 2020) proposed super-twisting nonsingular terminal sliding mode control for design and control of a lower limb rehabilitation robot, taking into account negative torques of the patient's limb to obtain the desired training missions; their results are comparable to those of adaptive sliding mode control. A Fuzzy Sliding Mode Controller (FSMC) was also proposed by (Maalej et al, 2020) for minimizing torques applied to a rehabilitation robot to help children, suffering from several diseases, to walk compared to the use of wheelchairs. Their simulation results show that the proposed controller is effective, moreover, it has been shown that the fuzzy sliding mode controllers are robust against parametric variations such as masses and lengths of kid's legs.…”
Section: Introductionmentioning
confidence: 99%
“…The sliding mode controller is generally utilized in industry and biomedical robots [15][16]. The controller can be planned regardless of the boundaries of the exploration model.…”
Section: Introductionmentioning
confidence: 99%